Recurrence of the plane Elephant random walk - Curien, Nicolas; Laulin, Lucile (Comptes Rendus. Mathématique)
We give a short proof of the recurrence of the two-dimensional elephant random walk in the diffusive regime. This was recently established by Qin (2023), but our proof mainly uses very rough comparison with the standard plane random walk. We hope that the method can be useful for other applications.